A Systematic Review of Teacher–Child Interactions With Multilingual Young Children. (August 2019) - Langeloo, Annegien; Mascareño Lara, Mayra; Deunk, Marjolein I.; Klitzing, Nikolai F.; Strijbos, Jan-Willem
Teacher–child interactions are the most important factor that determines the quality of early-childhood education. A systematic review was conducted to gain a better understanding of the nature of teacher–child interactions that multilingual children are exposed to, and of how they differ from teacher–child interactions of monolingual children. Thirty-one studies were included. The included studies (a) mainly focused on multilingual children with low language proficiency in the majority language and (b) hardly compared between monolingual and multilingual children. The review shows that teacher–child interactions of multilingual children are comparable to the interactions of monolingual children, although teachers do adopt different strategies to facilitate the development of multilingual children, such as the use of the home language and nonverbal communication to support understanding. Worryingly, several studies indicate that multilingual children are exposed to unequal learning opportunities compared with their monolingual peers.